1982
DOI: 10.1073/pnas.79.20.6401
|View full text |Cite
|
Sign up to set email alerts
|

Excluded-volume effect on quasi-elastic light scattering by flexible macromolecules

Abstract: First-order perturbation expressions are developed for the first cumulant (initial time derivative) of the dynamic structure factor observable by photon-correlation measurements of the light scattered by flexible chain molecules in solution. A dimensionless coefficient C, which measures the initial departure ofthe first cumulant from proportionality to the square ofthe scattering vector, is found to be only slightly altered by excluded-volume effects.Quasi-elastic light scattering (QELS) offers a powerful meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Thus, it cannot be explained well why, as described in Introduction, the experimental value is close to the results, 0.0625, calculated for non-PA nondraining chains. In this connection, it may be interesting to note a study by Tanaka and Stockmayer,19 who developed a first-order perturbation expression of by the same scheme as in the present work and showed that, for non-PA chains, limg_" Q/(q3kBT/q0) = 0.0625 independent of excluded volume. After all, we have the following suspicion that the discrepancies between experiments and theories for lim9^" Q/(q3kBT/q0) could be due to (1) the insufficiency of the Oseen description for the hydrodynamic interaction in the Kirkwood formula and/or (2) the approximate nature (or a lack of accuracy) of the Kirkwood formula.…”
Section: Discussionmentioning
confidence: 59%
“…Thus, it cannot be explained well why, as described in Introduction, the experimental value is close to the results, 0.0625, calculated for non-PA nondraining chains. In this connection, it may be interesting to note a study by Tanaka and Stockmayer,19 who developed a first-order perturbation expression of by the same scheme as in the present work and showed that, for non-PA chains, limg_" Q/(q3kBT/q0) = 0.0625 independent of excluded volume. After all, we have the following suspicion that the discrepancies between experiments and theories for lim9^" Q/(q3kBT/q0) could be due to (1) the insufficiency of the Oseen description for the hydrodynamic interaction in the Kirkwood formula and/or (2) the approximate nature (or a lack of accuracy) of the Kirkwood formula.…”
Section: Discussionmentioning
confidence: 59%
“…Although this result was first obtained by preaveraging the Oseen interactions, more sophisticated calculations show that only the constant of proportionality C depends on preaveraging,14 solvent quality,15 and combinations thereof. 16 In fact, this general result apparently holds for all systems with a single length scale and hydrodynamic interactions, including liquid consolute points, etc., so studies of the q-dependence of the mean relaxation rate merely allow one to measure the dimension d of space, in case there is any real uncertainty about that.…”
Section: Relaxation Of Internal Modesmentioning
confidence: 87%
“…Combining (18) with the definition of the Flory constant and (14) gives the dimensionless ratio (d = 3) (19) which reduces in the nondraining limit to (£, °°,£)/ 0 = [1 -13£/96(1 + £)]/[! -13£/64(1 + £)][1 + 0.224£/(l + £)] (20) In addition the intrinsic viscosity expansion factor of (17) is equal in this limit to The self-avoiding limit for (" = °» of (20) provides a lower bound ( / )nondraining (1 -13/96)/(l -13/64)(1 + 0.224) = 0.886 (22) to / 0 as a function of f in the nondraining limit.…”
Section: Intrinsic Viscosity Expansion Factormentioning
confidence: 99%